2023
DOI: 10.1021/acsnano.3c05282
|View full text |Cite
|
Sign up to set email alerts
|

Accumulative Delocalized Mo 4d Electrons to Bound the Volume Expansion and Accelerate Kinetics in Mo6S8 Cathode for High-Performance Aqueous Cu2+ Storage

Zhiguo Ren,
Yuanhe Sun,
Qi Lei
et al.

Abstract: Electronic structure defines the conductivity and ion absorption characteristics of a functional electrode, significantly affecting the charge transfer capability in batteries, while it is rarely thought to be involved in mesoscopic volume and diffusion kinetics of the host lattice for promoting ion storage. Here, we first correlate the evolution in electronic structure of the Mo 6 S 8 cathode with the ability to bound volume expansion and accelerate diffusion kinetics for high-performance aqueous Cu 2+ storag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…He et al demonstrated that anisotropic interplanar expansion of few-layer hexagonal NbS 2 nanosheets can balance the Cu 2+ intercalation, thus achieving an ultrastable Cu 2+ intercalation chemistry . Except for the aforementioned achievements made in the anode material, high-performance cathode materials with high capacity and accelerated kinetics have also been obtained through designing nanostructures. , This provides guidance for establishing energy storage devices with high energy density and rapid charge/discharge capability. Xu et al made high-capacity and high-power magnesium batteries a reality by using (NH 4 ) 2 MoS 4 as the cathode, in which NH 4+ could be extracted and form amorphous MoS 4 with plenty of active sites for Mg 2+ storage during the first discharge process .…”
Section: Nanochemistry and Environmental Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…He et al demonstrated that anisotropic interplanar expansion of few-layer hexagonal NbS 2 nanosheets can balance the Cu 2+ intercalation, thus achieving an ultrastable Cu 2+ intercalation chemistry . Except for the aforementioned achievements made in the anode material, high-performance cathode materials with high capacity and accelerated kinetics have also been obtained through designing nanostructures. , This provides guidance for establishing energy storage devices with high energy density and rapid charge/discharge capability. Xu et al made high-capacity and high-power magnesium batteries a reality by using (NH 4 ) 2 MoS 4 as the cathode, in which NH 4+ could be extracted and form amorphous MoS 4 with plenty of active sites for Mg 2+ storage during the first discharge process .…”
Section: Nanochemistry and Environmental Sciencementioning
confidence: 99%
“…The evolution of electronic structure in nanomaterials during the charge/discharge process may bring new opportunities for promoting transport kinetics. He and co-workers discovered that the Mo 4d electron evolution of nanosized Mo 6 S 8 reduced the volume expansion during Cu 2+ intercalation, thus promoting the diffusion kinetics for aqueous Cu 2+ storage …”
Section: Nanochemistry and Environmental Sciencementioning
confidence: 99%
“…Rechargeable batteries play an indispensable role in storing intermittent renewable energy and raise demands for more cost-effective, intrinsically safe, and eco-friendly alternatives to established lithium-ion batteries. [1][2][3][4][5][6] Driven by accessible potentials, high Clarke values, nontoxic and nonflammable electrolytes, and two-electron redox pairs, aqueous zinc ion batteries (AZIBs) have been revealed as promising candidates for energy storage devices with easily utilized high-energy metal anodes. [7][8][9][10] Significant efforts have been made to identify cathodes appropriate for aqueous systems to accommodate zinc ions and embrace more electron transfer, including Mn-oxides, [11][12] V-oxides, [13][14] Prussian blue analogs, [15][16] and transition-metal chalcogenides (TMCs).…”
Section: Introductionmentioning
confidence: 99%
“…Conversion reaction mechanism for electrodes in rechargeable energy storage devices implies the provision of high theoretical specific capacity and flat voltage plateau compared to ion intercalation and surface redox mechanisms, ensuring an appealing stable energy supply. [ 1 , 2 , 3 , 4 , 5 , 6 ] Driven by the potential high‐performance perspective, intensive efforts have been aimed at developing conversion‐type material electrodes for conventional lithium‐ion batteries and emerging aqueous batteries, including sulfur, [ 7 , 8 ] selenium, [ 9 , 10 ] tellurium, [ 4 , 11 ] and transition metal chalcogenides. [ 12 , 13 , 14 , 15 ] Nevertheless, the exploration of advanced conversion electrodes has been hindered by its major scientific challenges, especially in aqueous batteries with multivalent carriers; these challenges involve a significant capacity fading with undesirable operating life triggered by structural degradation at the microstructural and chemical bonding levels.…”
Section: Introductionmentioning
confidence: 99%